Environmental and social impacts for the cultivation of wheat with the mechanized raised bed method in Al-Sharqia governorate, Egypt - El-Kholy, Mohamed Ibrahim; Mohamed, Ghalia Mousa Ragab (Al-Mukhtar Journal of Sciences, 2016)
This research aims to estimate social and environmental impacts for wheat cultivation on the terraces using mechanized raised bed compared with other traditional methods. In addition, it aims at identifying the problems face farmers who do not adopt cultivating of wheat using mechanized raised bed and their suggestions to adopt such a way. A sample of 100 farmers using mechanized raised bed system has been chosen, in addition to 50 farmers using traditional methods of wheat cultivation. The collected data by questionnaire were analyzed by arithmetic average, Chi-square test, and One Way ANOVA. Among the social impacts of cultivation wheat with mechanized raised bed compared with traditional methods are: decreased number of required workers, increased the overall margin of man, increased incentive product and decreased the number of rural women workers. Concerning the environmental impacts, the study reveals the followings: decreased amounts of used fuel, chemical fertilizers and pesticides, increase the efficiency of weed control, regular improve of fertilizing. The effects on soil properties were: safe drainage of excess water, the preservation of low ground water level, regular distribution of water. The technical and physiological effects were: reduce crop lodging and increase the percentage of germination. The problems in using mechanized raised bed facing farmers were: lack of farmers cooperation in compilation of wheat areas to facilitate using mechanization, inadequate availability of machinery and lack of workers trained to use machines efficiently, lack of spare parts and maintenance centers, lack of information about machines, the absence of the role of agricultural extension and the weakness of agricultural mechanization services.